2022
DOI: 10.1177/10406387221125466
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and clinical performance of a fluorescence enzyme immunoassay for progesterone and determination of ovulation day in bitches

Abstract: We evaluated the performance of a third-generation fluorescence enzyme immunoassay kit (FEIA; Tosoh Bioscience) for progesterone (P4) measurement in canine serum to identify the day of luteinizing hormone (LH) peak and ovulation in bitches. We conducted P4 assays on 54 serum samples using a FEIA and a chemiluminescence immunoassay (CLIA; Siemens). For the FEIA kit, the linearity test, recovery test, inter- and intra-assay CVs, and total error observed (TEo) were calculated. Serum samples from 28 bitches were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, in the case of TSH, fT4, and TT3, previous studies have reported the use of these methods in dogs. [42][43][44][45][46][47][48] Additionally, for all of the methods applied, internal validation demonstrated good accuracy (coefficient of variation < 7%). The decision to make the sample population as homogeneous as possible in terms of age, physical activity, and breed certainly lent more robustness to the correlations identified but decreased the possibility of identifying subjects that, because of borderline thyroid function, had cycle phase-related variability that may have affected the proper diagnosis of euthyroidism.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, in the case of TSH, fT4, and TT3, previous studies have reported the use of these methods in dogs. [42][43][44][45][46][47][48] Additionally, for all of the methods applied, internal validation demonstrated good accuracy (coefficient of variation < 7%). The decision to make the sample population as homogeneous as possible in terms of age, physical activity, and breed certainly lent more robustness to the correlations identified but decreased the possibility of identifying subjects that, because of borderline thyroid function, had cycle phase-related variability that may have affected the proper diagnosis of euthyroidism.…”
Section: Discussionmentioning
confidence: 86%
“…This situation represents another limitation. However, in the case of TSH, fT4, and TT3, previous studies have reported the use of these methods in dogs 42‐48 . Additionally, for all of the methods applied, internal validation demonstrated good accuracy (coefficient of variation < 7%).…”
Section: Discussionmentioning
confidence: 92%
“…In view of the diverse requirements for precise diagnostics and well-considered decision-making, veterinarians consider commercial immunological analyzers indispensable. Several researchers have reported the accuracy of other commercial point-of-care immunologic analyzers compared with gold-standard methods, such as RIA, LC-MS, and computed tomography (CLIA) [ 5 , 18 20 , 30 ]. However, the present study is the first to report the use of the Vcheck ® analyzer, providing novel insights into its accuracy and application.…”
Section: Discussionmentioning
confidence: 99%
“…Singleton pregnancies, fetal heart rate alterations with values lower than 160 bpm ( 23 ), fetuses with US evidence of morphological abnormalities, a stillbirth rate ≥ 30%, the neonatal death of the monitored fetuses or elective C-section, performed before serum progesterone drop (progesterone > 2 ng/ml) were also considered as exclusion criteria. For progesterone assay, the serum samples were analyzed with a fluorescence enzyme immunoassay (FEIA) method using an Automated Immunoassay Analyzer 360 (AIA ® 360, TOSOH Corp., Japan) ( 24 ). Therefore, bitches in which the US monitoring days were based on fetometry were excluded if, after delivery, the US monitoring days counted backward from the parturition day (day 0) were not in the defined time range.…”
Section: Methodsmentioning
confidence: 99%